Notes on the Ethnobotany of Costa Rica's palms - Sylvester, Olivia (2012)
To support the implementation of policies that recognize human uses of wild plants, we documented palm ethnobotany within or bordering eight protected areas in Costa Rica. Through participant observation and semi-structured interviews with 37 participants from 18 communities, we documented the cultivation and harvest of 32 palm species from 21 genera. We also reported uses of five palms (Cryosophila warscewiczii, Bactris gasipaes, Desmoncus costaricensis, Elaeis oleifera, Pholidostachys pulchra) that, to our knowledge, were previously undescribed in the literature.